FAKTOR YANG MEMPENGARUHI RETURN SAHAM DENGAN MODERATOR KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR - Nathalia Andriani; Rini Tri Hastuti (Jurnal Paradigma Akuntansi, 2023)
This research aims to see how the influence of firm size, leverage, and investment opportunity settings on stock returns with dividend policy as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019. The sample was selected by purposive sampling method and the valid data were 52 companies. The data processing technique uses multiple regression analysis assisted by the EViews 10 and Microsoft Excel 2010 programs. The results of this study indicate that the influence and investment opportunities have a significant effect on stock returns, and dividend policy is able to moderate the effect of established investment opportunities on stock returns. The implication of this research is the need for investors to pay attention to the level of debt that the company uses in financing the company's operating activities, as well as the size of theset of investment opportunity set the company has which can affect the stock returns that investors will receive.